PENSION REFORM IN THE EUROPEAN PERIPHERY: THE ROLE OF EU REFORM ADVOCACY. (October 2014) - Stepan, Matthias; Anderson, Karen M.; Collins, Paul D.; Podger, Andrew; Dong, Keyong
SUMMARY This paper analyzes the impact of international reform advocacy on national pension reforms. We analyze European Union (EU) reform advocacy in two EU member states: Greece and Hungary. Although the EU has articulated a fairly coherent template for sustainable pensions, its use of soft coordination to influence national reforms has repeatedly collided with resistance to reform in the member states. As a result, EU soft law initiatives have had limited impact on pension reforms. In contrast, the sovereign debt crisis that began in 2009 provided a new push for EU reform advocacy because it gave the "troika" (the European Commission, European Central Bank and International Monetary Fund) substantial influence on pension reform in two countries affected by the debt crisis: Greece and Hungary. Analysis of the two countries' pension reform trajectories allows us first to determine to what extent Greek and Hungarian pension reforms conform to the EU's reform template and, second, how the troika conditionality has a causal impact on the content of reforms in both countries. Copyright © 2014 John Wiley & Sons, Ltd.